BIOLOGICAL ACTIVITIES OF SCHEFFLERA LEUCANTHA - Potduang, Dr. Buppachart -; Chongsiriroeg, Mr. Chanchai -; Benmart, Ms. Yaowaluck -; Giwanon, Mrs. Rattanasiri -; Supatanakul, Mr. Winai -; Tanpanich, Mr. Sayan - (African Journal of Traditional, Complementary and Alternative Medicines, 2006)
This study investigated various biological activities of the ethanolic extract of dried ground leaves of Schefflera leucantha Viguier (Araliaceae). The extract possessed very low cytotoxicity to brine-shrimp with the LC50 of 4,111.15μg/ml; the significant antioxidant activity on DPPH with the EC50 of 71.90μg/ml; the inhibitory activity on mushroom tyrosinase with the IC50 of 10.53mg/ml using the dopachrome microplate-assay. The extract of 5-20mg/ml range in the agar dilution assay were active against various pathogenic microbial (11 species, 11 strains), with the minimum inhibitory concentration (MIC) of 5mg/ml against Clostridium spp.; MIC=10mg/ml against enteropathogens as Bacteroides spp., Enterococcus faecalis ATCC 29212, Lactobacillus spp., Peptococcus spp. and Streptococcus mutans; MIC=10mg/ml against a pneumonia causing bacteria Klebsiella pneumoniae and a dermatopathogen as Propionibacterium acnes; MIC=20mg/ml against dermatopathogens as Staphylococcus aureus ATCC 6538, Streptococcus spp. and Candida albicans ATCC 90028. TLC fingerprints of the specific extracts from the leaf powder exhibited zones of steroids-terpenes and flavonoids. HPLC fingerprint of the flavonoid extract was performed. Key words: Schefflera leucantha, Antioxidant, Antityrosinase, Antimicrobial activity, Phytochemistry